A new political system model: Semi‐parliamentary government. (26th July 2017) - GANGHOF, STEFFEN
Abstract: Semi‐parliamentary government is a distinct executive‐legislative system that mirrors semi‐presidentialism. It exists when the legislature is divided into two equally legitimate parts, only one of which can dismiss the prime minister in a no‐confidence vote. This system has distinct advantages over pure parliamentary and presidential systems: it establishes a branch‐based separation of powers and can balance the 'majoritarian' and 'proportional' visions of democracy without concentrating executive power in a single individual. This article analyses bicameral versions of semi‐parliamentary government in Australia and Japan, and compares empirical patterns of democracy in the Australian Commonwealth as well as New South Wales to 20 advanced parliamentary and semi‐presidential systems. It discusses new semi‐parliamentary designs, some of which do not require formal bicameralism, and pays special attention to semi‐parliamentary options for democratising the European Union.